Self-Consistent Two-Gap Approach in Studying Multi-Band Superconductivity of NdFeAsO0.65F0.35 - Gupta, Ritu; Maisuradze, Alexander; Zhigadlo, Nikolai D.; Luetkens, Hubertus; Amato, Alex; Khasanov, Rustem (Frontiers in Physics, 2020)
High quality single crystals of NdFeAsO_0.65F_0.35 (the superconducting transition temperature T_c30.6 K) were studied in zero-field (ZF) and transverse-field (TF) muon-spin rotation/relaxation (μSR) experiments. An upturn in muon-spin depolarization rate at T3 K was observed in ZF-μSR measurements and it was associated with the onset of ordering of Nd electronic moments. Measurements of the magnetic field penetration depth (λ) were performed in the TF geometry. By applying the external magnetic field B_ex parallel to the crystallographic c-axis (B_ex\| c) and parallel to the ab-plane (B_ex\| ab), the temperature dependencies of the in-plane component (λ_ab^-2) and the combination of the in-plane and the out of plane components (λ_ab,c^-2) of the superfluid density were determined, respectively. The out-of-plane superfluid density component (λ_c^-2) was further obtained by combining the results of B_ex \| c and B_ex \| ab set of experiments. The temperature dependencies of λ_ab^-2, λ_ab,c^-2, and λ_c^-2 were analyzed within the framework of a self-consistent two-gap model despite of using the traditional α-model. Interband coupling was taken into account, instead of assuming it to be zero as it stated in the α-model. A relatively small value of the interband coupling constant Λ_12 0.01 was obtained, thus indicating that the energy bands in NdFeAsO_0.65F_0.35 are only weakly coupled. In spite of their small magnitude, the coupling between the bands leads to the single value of the superconducting transition temperature T_c. The penetration depth anisotropy γ_λ=λ_c/λ_ab was found to increase upon cooling, consistent with most of Fe-based superconductors, and their behavior is attributed to the multi-band nature of superconductivity in NdFeAsO_0.65F_0.35.